Nanog promotes osteogenic differentiation of the mouse mesenchymal cell line C3H10T1/2 by modulating bone morphogenetic protein (BMP) signaling1. Issue 1 (4th October 2012) - Ogasawara, Toru; Ohba, Shinsuke; Yano, Fumiko; Kawaguchi, Hiroshi; Chung, Ung‐il; Saito, Tadahito; Yonehara, Yoshiyuki; Nakatsuka, Takashi; Mori, Yoshiyuki; Takato, Tsuyoshi; Hoshi, Kazuto
Abstract How the pluripotency of stem cells is maintained and the role of transcription factors in this maintenance remain major questions. In the present study, in order to clarify the mechanism underlying the pluripotency of stem cells for the advancement of regenerative medicine, we examined the effect of forced Nanog expression in mesenchymal cells, with a particular focus on osteogenic differentiation. The human mesenchymal stromal cells (hMSCs) or mouse mesenchymal cell line C3H10T1/2 cells were transduced with the Nanog gene or control green fluorescent protein (GFP) gene by using retrovirus vectors. Short‐term, forced Nanog gene expression had few effects on the terminal osteogenic differentiation of either hMSCs or C3H10T1/2 cells. To determine its long‐term effects, we established C3H10T1/2 cells expressing Nanog constitutively. Constitutive Nanog expression strongly induced osteogenic differentiation of C3H10T1/2 cells. In regard to cell proliferation, constitutive Nanog expression only repressed the proliferation of the cells treated with rhBMP‐2. Moreover, Nanog also had the potential to promote the proliferation of C3H10T1/2 cells in the absence of rhBMP‐2. Constitutive Nanog expression enhanced phosphorylation of Smad1/5/8 and suppressed Cdk4 and cyclinD1. The promoter activities of both the osteocalcin and Id‐1 genes were activated in cells expressing Nanog constitutively. To identify downstream molecules of Nanog involved in the promotion of osteogenic differentiation, we performed a DNA microarray analysis and discovered that NFATc1 was one of the downstream effectors of Nanog. These results indicate that Nanog functions as a modulator of BMP signaling in C3H10T1/2 cells probably through a genome reprogramming process. J. Cell. Physiol. 228: 163–171, 2013. © 2012 Wiley Periodicals, Inc.